Elan Corporation turnaround - Shein, James B., 1942-; Anstey, Robert; Lang, Nathan ([London] : SAGE, 2016)
The case begins with newly appointed chairman and interim CEO Garo Armen dwelling on the significant issues that Elan Corporation, an Irish pharmaceutical company, faces. Its share price has plummeted 96% after accusations of accounting fraud and the discontinuation of an important clinical trial due to the drug's severe side effects. As a result, Elan faces insolvency. About $2 billion in debt that could no longer be satisfied in stock will soon mature, and there are questions regarding the company's structure and various operating concerns.
Originally Published in: Shein, J., Anstey, R., & Lang, N. (2010). Elan Corporation Turnaround. 5-210-262. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Elan Corporation; Corporate turnarounds -- Case studies; Corporations -- Finance -- Case studies; Corporate governance -- Case studies